Sensible al código. Transferencias metodológicas entre saberes ancestrales y nuevos medios para la dividuación - Portal Carrasco, Fernando Andrés.; Schultz, María Jesús (Universitat Oberta de Catalunya, 2023)
This article compiles the experience of Sensible al Código (Sensitive to code), a practice-based research, which explores, through the production of artistic works, non-western cosmologies as a basis for the application of machine learning algorithms. The aim of this is to explore methodologies of artistic creation that incorporate ancestral knowledge as a basis for the development and preservation of technodiversities, in the context of the cosmotechnics proposal of Yuk Hui. To do this, the article begins by characterizing the cosmology and rituals pertaining to the relational ontology of the shipibo-konibo people of the Amazon, from a viewpoint informed by the perspectivism of Viveiros de Castro and the divid-ualist animism of Bird-David. These rituals are unfolded as a method, through an analysis informed by media theory and anthropology, which is then applied in machine learning processes and in the materialization of the images obtained, through artistic considerations of their physical, visual, tactile and sound properties. Finally, the reflection informed by bodily interaction with these works and the agentiality of their materials will offer up as a conclusion the possibility of repositioning ourselves as part of a continuous flow of energy exchange, enabling speculation on the potential of these transferences to cause cosmotechnical bifurcations.
Sensible al código. Methodological transference between ancestral knowledges and new means of dividuation
Keywords: Nuevo animismo; Cosmotécnicas Latinoamericanas; Cosmovisiones amazónicas; Investigación basada en práctica; Aprendizaje de máquina